Plot of ATU 160 in Oirat Monument “Tale of Nectar Teaching” - B. V. Menyaev (Научный диалог)
The article continues the study of the Oirat monument “The Tale of Nectar Teaching” (“Aršāni nomiyin tuuǰi”). Three unpublished manuscript lists are introduced into scientific circulation. For the first time, the international plot ATU 160 “Grateful Animals. Ungrateful Man. Salvation from the Pit” is considered based on four stories from “The Tale of Nectar Teaching”. The source of the study was the lists “Aršāni nomiyin tuuǰi”, stored in the manuscript department and archive of Orientalists at the Institute of Oriental Studies, Russian Academy of Sciences, and the Scientific Library of the Eastern Faculty of St. Petersburg State University. Catalogs, indexes with international plots, folklore materials, translations of written monuments in Tibetan, Chinese, ancient Indian and Mongolian languages were used as additional materials. It is shown that all analyzed works represent a holistic picture of the ATU 160 plot, complementing each other. Common characteristics are identified, among which the most stable is the same composition. It is noted that the texts end with an explanation and a moral lesson. It is asserted that the basis of the ATU 160 plot is foreign material, which is slightly transformed in the compositions. The author concludes that the plot “Grateful Animals; Ungrateful Man. Salvation from the Pit”, presented in different works, is evidence of the unity of the IndoTibetan-Mongolian-Oirat literary fund.